Src homology phosphotyrosyl phosphatase‐2 expression is an independent negative prognostic factor in human breast cancer. Issue 1 (15th May 2013) - Muenst, Simone; Obermann, Ellen C; Gao, Feng; Oertli, Daniel; Viehl, Carsten T; Weber, Walter P; Fleming, Timothy; Gillanders, William E; Soysal, Savas D
<x xml:space="preserve">Abstract</x> Aims Src homology phosphotyrosyl phosphatase‐2 (SHP2) is a ubiquitously expressed phosphatase that plays an essential role in the downstream signalling pathways of multiple growth factor receptors, thus representing a potential target for cancer therapy. Recent studies suggest that SHP2 contributes to tumour initiation, progression and metastasis in breast cancer, yet the impact of SHP2 expression on prognosis in human breast cancer has not been evaluated. Methods and results To explore further the role of SHP2 in breast cancer, we conducted an immunohistochemical study using a tissue microarray encompassing 1401 formalin‐fixed breast cancer specimens with detailed clinical annotation and outcome data. Of 1401 evaluable breast cancers, 651 (46%) were positive for SHP2. SHP2 expression was associated positively with tumour grade, lymph node status and tumour stage. In univariate survival analysis, cases with SHP2 expression had a significantly worse overall survival (OS). In multivariate analysis, SHP2 remained an independent negative prognostic factor for OS. SHP2 expression was a negative prognostic factor for OS in the luminal A and the luminal B HER2− intrinsic subtypes. Conclusions Our data demonstrate for the first time that SHP2 is an independent predictor of survival in breast cancer, suggesting that SHP2 may be a potential target for therapy.